Do Individuals with Misophonia Experience Challenges with Their Auditory Binaural Interaction and Integration Skills? - Hrishitha Valia Madappally; Kavassery Venkateswaran Nisha; Prashanth Prabhu (Auditory and Vestibular Research, 2024)
Background and Aim: Misophonia is a condition marked by heightened sensitivity and intense emotional and physiological responses to particular sounds that may not spark the same reactions in others. This study is the first of its kind to assess binaural integration and binaural interaction in misophonia. Methods: Thirty misophonia and 30 control participants were considered in the age range of 18 to 30 years. All the participants had hearing sensitivity within normal limits and normal middle ear function. Individuals with a history of otological complaints, noise exposure, ototoxic medications, tinnitus, hyperacusis, diabetes, or hypertension were excluded from the study. Misophonia severity was assessed using the Misophonia Assessment Questionnaire (MAQ). Binaural integration was assessed using Dichotic Consonant Vowel (DCV) test, and binaural interaction was assessed using Masking Level Difference (MLD). Results: The statistical analysis of the independent t-test for DCV and Mann Whitney U test for MLD showed no significant difference between misophonia and the control group for both MLD and DCV. Conclusion: The results suggest that there is no significant difference in DCV and MLD scores between the control and misophonia groups.